Analisis Faktor Keberhasilan dan Hambatan Implementasi Rekam Medis Elektronik di Rumah Sakit (Literratur Review) - Nunung Setiyawati; Edy Susena (STIKES Columbia Asia Medan, 2026)
The implementation of Electronic Medical Records (EMR) has become an essential part of digital transformation in the healthcare sector, aiming to improve the quality, effectiveness, efficiency, and continuity of healthcare services. In Indonesia, the implementation of EMR is supported by the Regulation of the Minister of Health Number 24 of 2022, which mandates healthcare facilities to adopt electronic medical records. However, the implementation process is often challenged by various technical and non-technical factors that may affect its success. This study aims to analyze the success factors and barriers to EMR implementation in hospitals through a literature review approach. The research method used was a literature review by examining and analyzing 11 scientific articles obtained from Google Scholar and other relevant scientific sources. The findings indicate that the success of EMR implementation is influenced by three main aspects, namely human, organizational, and technological factors. Supporting factors include management commitment, user readiness, continuous training, availability of information technology infrastructure, system quality, and organizational support. Meanwhile, common barriers include limited digital literacy among healthcare workers, insufficient information technology personnel, unstable internet connectivity, system errors, inadequate facilities and infrastructure, budget limitations, and the absence of specific standard operating procedures. Furthermore, EMR implementation provides significant benefits, such as improving service efficiency, facilitating access to patient information, enhancing documentation quality, supporting communication among healthcare professionals, and increasing patient safety. Therefore, successful EMR implementation requires synergy between human resources, organizational readiness, and technological infrastructure to achieve optimal healthcare service delivery.